Video re-sampling and content re-targeting for realistic driving incident simulation - Heras, Alejo M.; Breckon, Toby P.; Tirovic, Marko (Cranfield University, 2011)
We present a video generation and visualization system for integration into a driving incident simulator. We combine the use of video re-sampling, target tracking and object segmentation for content re-targeting to generate realistic video content that can be adapted on demand, based upon simulator inputs to generate a range of driver incident test scenarios
Keywords: Motion Frame Rate Up-Converters (MFRUC), frame interpolation, object segmentation, feature tracking